La Gestalt-Play-Therapy: un intervento psicoterapeutico integrato per le famiglie - oncologiche - 1 Miriam Abbate, 1 Angela Ciulla, 1 Letizia Cacciabaudo, 1 Francesco Paolo Scarito (Marp Edizioni, 2020)
The diagnosis of a neoplastic disease brings with it the experience of body pain, sadness, fear of death, detachment from everyday life; this is experienced by both the patient and the family. The "stress of cancer disease" is experienced as "family disease". Hence the term family-oncology. The aim of the research is to evaluate: (1) the effectiveness of Gestalt-Play-Therapy (G.P.T) in oncology wards with patients and family members (2) moderate levels of di-stress in the family-oncology (3) increase awareness of needs, emotions through the game. Working only on suffering often does not help, especially if the disease cannot be cured. Help for the patient and the family can be to use the G.P.T to improve health and psychological well-being. Exploring what is behind the suffering helps to find a new way to live despite the diagnosis. Sample: 40 patients and caregivers divided into groups: (1) classical program (2) Gestalt Play therapy psychotherapy group. Method: Group, G.P.T techniques, questionnaires administration: - PSS,Perceived Stress Scale  - BAI Beck anxiety inventory self-report test to measure anxiety - The multidimensional scales of pain Brief Pain Inventory - GPTIO Gestalt Play Therapy Test in Oncological phenomenological test in planning Results: we hypothesize a reduction of anxiety and di-stress in the cancer family, an improvement in lifestyle, better ability to satisfy needs, greater awareness and acceptance of the disease. Conclusions: Prevention of traumatic experience, better awareness of the disease and the ability to meet the needs of the cancer family are expected